The mighty Thor. Vol. 3. The Asgard/Shi'ar war - Aaron, Jason (Thor., 2017)
"Thor must deal with the escalating war of the Realms! To face Malekith, Loki and an all-new Kurse, she'll need a team of her own. Prepare for the triumphant return of the League of Realms! Far across the galaxy, though, another conflict is brewing--as the most powerful super-army in the cosmos prepares a surprise attack on the city of the gods! The Shi-ar Empire will lay siege to Asgardia--and their target is the Goddess of Thunder! But why? And what does the fate of Midgard have to do with it? And where the Shi'ar go, the Phoenix Force tends to follow--which is bad news for Thor! Maybe the returning Odinson could lend a hand--or perhaps the rebel X-Man known as Quentin Quire?!" -- cover.